Epigenetics in autoimmune connective tissue diseases - Delsante, Giovanni; Fietta, Pieranna (Acta Biomedica Atenei Parmensis, 2014)
Background. Autoimmune connective tissue diseases (ACTDs) encompass a heterogeneous group of chronic immune-mediated inflammatory disorders, primarily affecting connective tissues and clinically characterized by variable multisystem manifestations, frequently overlapping. Environmental factors are thought to promote ACTD development in genetic predisposing/endocrine permissive background through the induction of epigenetic modifications, consisting of stable, heritable, but potentially reversible changes in gene expression, occurring without alterations of the DNA sequence. Actually, epigenetic mechanisms (such as histone modifications, DNA methylation, nucleosome positioning, and RNA interference) link genotype upstream and phenotype downstream, and, if persistently aberrant, may cause a variety of human diseases, including ACTDs. We aimed to review the recent advances in the knowledge of the ACTD epigenetic alterations. Methods: A detailed search of the available literature was performed in the PubMed (U.S. National Library of Medicine) database. Results: Growing evidence underlines the relevant role of epigenetic defects in the ACTD pathogenesis, and specific epigenetic patterns can represent disease biomarkers. In patients with rheumatoid arthritis (RA), epigenetic variations interact determining the typical “aggressive” phenotype displayed by RA synovial fibroblasts. Epigenetic modifications are involved in the profibrotic process that characterizes systemic sclerosis. In systemic lupus erythematosus and Sjögren’s syndrome, complex epigenetic changes altering gene expression have been demonstrated. Conclusions: Comprehensive studies will contribute to further define the aberrant epigenetic mechanisms involved in the ACTDs etiopathogenesis. Moreover, being epigenetic changes potentially reversible, the identification of ACTDs epigenetic biomarkers will allow the development of therapeutic strategies addressed to target dysregulated genes and correct aberrant epigenomic alterations.